Treatment of Oral Vascular Malformations with Ethamolin: A Report of Two Cases - Coelho Ferreira, Maria Clara de Moura Santos; de Sales Lima, Marco Vinícius; Almeida Barreto, Anna Laura; Kitakawa, Dárcio; Scherma, Alexandre do Prado; Peralta, Felipe; de Carvalho, Luis Felipe das Chagas e Silva (UI Scholars Hub, 2023)
A hemangioma is a benign vascular neoplasm, relatively common in the head and neck. In the oral region, it affects the tongue, gums, mucosa, palate, and lip. Its size can vary from millimeters to centimeters, characterized as a purplish or reddish lesion. The present study aims to present two clinical cases of hemangiomas, the first of a male patient treated by sclerotherapy and the second of a female patient in which she was treated with ethamolin and later surgical treatment. It was concluded that sclerotherapy, in addition to being a safe treatment, managed to drastically reduce the initial size of the lesions present in this article.